Concentrated joint wires, wires with terminals, and methods for manufacturing the same.

JP2026165293APending Publication Date: 2026-10-14FURUKAWA ELECTRIC CO LTD +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2025057613
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2025-03-31
Publication Date
2026-10-14

AI Technical Summary

Benefits of technology

【0035】 本発明によれば、厚みのある硬化樹脂を有する場合であっても、硬化時間を短くするとともに、配索後の周囲の温度上昇によって深部にある樹脂まで十分に硬化させて、水分の導体部分への浸入に対する止水性を高めることが可能な集中ジョイント電線および端子付き電線と、それらの製造方法を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2026165293000001_ABST
    Figure 2026165293000001_ABST
Patent Text Reader

Abstract

The present invention provides a concentrated joint wire and a wire with terminals that, even with a thick curing resin, can shorten the curing time and allow the resin to fully cure to its depths due to the rise in ambient temperature after wiring, thereby improving watertightness against the intrusion of moisture into the conductor portion. [Solution] The centralized joint wire 1 has a joint 15 formed by stripping the insulating coating layers 12a to 12g covering the ends of multiple insulated wires 10a to 10g to expose the conductors 11a to 11g at the ends, and joining and integrating the bundled exposed conductor portions 14. The joint 18 consists of an inner resin portion 16 made of cured resin that is integrally formed with the joint 15 in close contact with at least the entire outer surface 15a of the joint 15, and an outer resin portion 17 that is integrally formed in close contact with at least the entire outer surface 16a of the inner resin portion 16. The cured resin has a gel fraction after a heating test of heating at 120°C for 1 hour that is higher than the gel fraction before the heating test.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] This invention relates to a centralized joint wire, a wire with terminals, and a method for manufacturing the same. [Background technology]

[0002] In wire harnesses routed inside vehicles such as automobiles, branch lines are often branched from main lines or main lines are connected in series to connect multiple wires to each other. One example of such a connecting wire is one that has a splice section where multiple wires are electrically connected by bundling the exposed conductor portions at the ends of multiple insulated wires with their insulation stripped off, and then crimping a connecting component such as a splice terminal onto them.

[0003] Furthermore, electrical wiring such as wire harnesses routed inside vehicles uses wires with terminals attached, where a metal terminal (connector) is attached to the exposed conductor portion, which is the conductor portion exposed by stripping the insulating coating at the end of the insulated wire.

[0004] To prevent water from entering the conductor portion of such terminal-equipped electric wires, waterproofing materials made of resin or the like have been conventionally known. These materials are applied to the surface of the exposed conductor to block contact between the exposed conductor and water or electrolytes, thereby preventing water from entering. Liquid resins are preferred as waterproofing materials because they can be applied to conform to the surface shape of the exposed conductor, which has a complex three-dimensional shape. Curable resins are often used to improve the adhesion of the resin material to the exposed conductor after application, and to enhance heat resistance and chemical resistance when routed in vehicles or the like.

[0005] For example, Patent Document 1 describes an ultraviolet-curable resin mainly composed of a polymerizable compound consisting of at least one of a photopolymerizable (meth)acrylate monomer and a photopolymerizable (meth)acrylate oligomer, wherein the polymerizable compound is obtained by using a monofunctional (meth)acrylate monomer having one functional group having a carbon-carbon unsaturated bond and a difunctional (meth)acrylate monomer having two such functional groups, or by using at least one of a monofunctional (meth)acrylate monomer and a difunctional (meth)acrylate monomer and at least one of a trifunctional (meth)acrylate monomer having three such functional groups and a polyfunctional (meth)acrylate monomer having four or more such functional groups, and the viscosity at 25°C measured in accordance with JIS Z 8803 is 18900 mPa·s or less. This corrosion inhibitor prevents corrosion of exposed electrical wires by preventing water from seeping into the exposed parts. It uses an ultraviolet-curing resin that mixes (meth)acrylate monomers with a low number of functional groups and (meth)acrylate monomers with a high number of functional groups. As a result, the cured product has an appropriate crosslinking density, which improves not only strength, hardness, and surface hardness, but also elongation and deep hardening properties. [Prior art documents] [Patent Documents]

[0006] [Patent Document 1] Patent No. 6200448 [Overview of the project] [Problems that the invention aims to solve]

[0007] However, with UV-curing resins and moisture-curing resins, if the thickness of the curing portion is large, even if the curing performance is high near the surface, the curing performance in the deeper parts in the thickness direction will be low. In particular, near conductors and terminals, and in the deeper parts that are shaded by conductors, the adhesion between the conductor or terminal and the resin, as well as the heat resistance and chemical resistance of the resin, will decrease, which may lead to delamination of the resin, and thus the watertightness against the intrusion of moisture into the conductor or terminal may decrease. Furthermore, if the curing performance in the deeper parts is low, the heat resistance when routed in vehicles may also decrease.

[0008] Furthermore, the waterproofing material described in Patent Document 1 uses an ultraviolet-curable resin that is a mixture of (meth)acrylate monomers with a small number of functional groups and (meth)acrylate monomers with a large number of functional groups. As a result, the cured product (sealant) obtained has an appropriate crosslinking density, and it is stated that it is possible to improve not only strength, hardness and surface hardness, but also elongation and deep hardening properties. However, the ultraviolet-curable resin described in Patent Document 1 has limitations in deep hardening properties when cured with ultraviolet light. For example, even if it was possible to harden to the depths of a thin 2 sq aluminum wire with terminals as shown in the example in Patent Document 1, in thicker aluminum wires with terminals of 8 sq or more, or in jointed wires where the conductor parts of multiple wires are joined together, the thickness of the waterproofing film increases, resulting in lower deep hardening properties of the ultraviolet-curable resin, i.e., hardening properties in the depth direction. Therefore, particularly near conductors and terminals, and in deeper areas that are shaded by conductors, the adhesion between the conductors / terminals and the resin, as well as the heat resistance and chemical resistance of the resin, may decrease, potentially leading to delamination of the resin. This could reduce the water-sealing properties against moisture penetration into the conductors and terminals. Furthermore, if the curing properties in deeper areas are low, the heat resistance when routed in vehicles may also decrease.

[0009] On the other hand, with regard to thermosetting resins among curable resins, a problem arises because heating is required until curing is complete in the deeper parts in the thickness direction in order to improve watertightness against the penetration of moisture into the conductive parts. This necessitates a longer heating time during the curing process.

[0010] In this regard, given the recent proactive efforts to reduce greenhouse gas emissions, there is a need to shorten heating processes in manufacturing wire harnesses and other applications. In particular, there has been a demand to shorten the heating time in the curing process, especially when curing thermosetting resins with a large thickness of curing portion.

[0011] Furthermore, in recent years, the variety of driving assistance and safety features installed in automobiles has been increasing year by year. To connect the electronic devices used in these driving assistance and safety features, the number of wire harnesses used in automobiles has also increased. In addition, in the centralized joint wires used in these wire harnesses, the diameter of the joint section has increased due to the increase in the number of conductors of the wires that are joined together and the increase in the value of the current flowing through them. Similarly, the diameter of the wires is also increasing in the terminal wires used in these wire harnesses. In such centralized joint wires and terminal wires, depending on the location where they are routed in a vehicle or other facility, the ambient temperature can rise to around 120°C. At the same time, it is necessary to use a resin with increased thickness and improved insulation to seal the conductor section. However, UV-curing resins such as those described in Patent Document 1 cannot sufficiently cure the resin deep inside.

[0012] The object of the present invention is to provide a concentrated joint wire and a wire with terminals, and a method for manufacturing them, which can shorten the curing time even when a thick cured resin is present, and can sufficiently cure the resin even in the deeper parts due to the rise in ambient temperature after wiring, thereby improving watertightness against the penetration of moisture into the conductor portion. [Means for solving the problem]

[0013] The inventors have discovered that by using a curing resin that, when a concentrated joint wire or a wire with terminals has at least one portion of the coating resin that is in contact with the conductor, the gel fraction after heating (the gel fraction after heating) is higher than the gel fraction before heating (the gel fraction before heating) when a heating test is performed at 120°C for 1 hour, even if the curing resin is thick, the resin deep within the conductor portion hardens due to the rise in ambient temperature after wiring, thereby improving the watertightness against the penetration of moisture into the conductor portion, and thus completing the present invention.

[0014] (1) A concentrated joint wire comprising a plurality of coated wires, each having a conductor and an insulating coating layer covering the conductor, wherein the insulating coating layer covering each end of the plurality of coated wires is stripped to expose the conductor portion at the end, and the exposed conductor portions are bundled together and joined to form a joint, wherein the concentrated joint wire has a coating resin portion comprising an inner resin portion made of a cured resin that is integrally formed with the joint in a state of close contact over at least the entire outer surface of the joint, and an outer resin portion that is integrally formed in a state of close contact over at least the entire outer surface of the inner resin portion, wherein the gel fraction after heating, which is the gel fraction after a heating test of heating at 120°C for 1 hour, is higher than the gel fraction before heating, which is the gel fraction before the heating test.

[0015] (2) The concentrated joint electric wire according to (1) above, wherein the gel fraction of the cured resin after heating is 12.5% ​​or more higher than the gel fraction before heating.

[0016] (3) The concentrated joint electric wire according to (2) above, wherein the gel fraction of the cured resin after heating is 25.0% or more higher than the gel fraction before heating.

[0017] (4) The concentrated joint electric wire according to (3) above, wherein the gel fraction of the cured resin after heating is 50.0% or more higher than the gel fraction before heating.

[0018] (5) The concentrated joint electric wire according to any one of the above (1) to (4), wherein the cured resin is a thermosetting resin.

[0019] (6) The concentrated joint electric wire according to the above (5), wherein the cured resin further has one or more curability selected from ultraviolet curability, moisture curability and anaerobic curability.

[0020] (7) The concentrated joint electric wire according to the above (1), wherein the inner resin portion has a thickness in a range of 3.0 mm or more and 15.0 mm or less.

[0021] (8) An electric wire with terminal, comprising: a covered electric wire having an insulating coating layer coated on a surface of a conductor; and a metal terminal electrically connected to a conductor portion exposed by stripping the insulating coating layer covering an end portion of the covered electric wire, wherein a coating resin portion made of a cured resin is formed by coating at least on an outer surface of the exposed conductor portion of the covered electric wire, and the cured resin has a post-heating gel fraction which is a gel fraction after a heating test of heating at 120°C for 1 hour, the post-heating gel fraction being higher than a pre-heating gel fraction which is a gel fraction before the heating test is performed.

[0022] (9) The electric wire with terminal according to the above (8), wherein the post-heating gel fraction of the cured resin is higher by 12.5% or more than the pre-heating gel fraction.

[0023] (10) The electric wire with terminal according to the above (9), wherein the post-heating gel fraction of the cured resin is higher by 25.0% or more than the pre-heating gel fraction.

[0024] (11) The electric wire with terminal according to the above (10), wherein the post-heating gel fraction of the cured resin is higher by 50.0% or more than the pre-heating gel fraction.

[0025] (12) The electric wire with terminal according to any one of the above (8) to (11), wherein the cured resin is a thermosetting resin.

[0026] (13) The terminal wire as described in (12) above, wherein the curing resin further has one or more curing properties from ultraviolet curing, moisture curing, and anaerobic curing.

[0027] (14) The wire with a terminal as described in any one of items (8) to (13) above, wherein the length of the portion of the covering resin that faces the area from the end to the bottom of the inner wall of the metal terminal is in the range of 3.0 mm to 15.0 mm.

[0028] (15) A wire harness comprising one or both of the concentrated joint wires described in any one of items (1) to (7) above and the terminal wires described in any one of items (8) to (14) above.

[0029] (16) A method for manufacturing a concentrated joint electric wire having a joint formed by bundling and joining together a plurality of insulated electric wires, each having a conductor and an insulating coating layer covering the conductor, by stripping the insulating coating layer covering each end of the insulated electric wire to expose the conductor portion at the end, the insulated electric wire having an insulating coating layer covering the conductor, the method comprising: a resin immersion step of immersing at least the joint in an outer resin portion filled with a curable resin; and a resin curing step of curing the curable resin in which at least the joint has been immersed in the outer resin portion to form an inner resin portion, thereby forming an inner resin portion, the insulated resin portion and the outer resin portion forming a coated resin portion that is integrally formed in close contact over at least the entire outer surface of the joint, wherein the resin curing step involves curing the curable resin such that the gel fraction after heating, which is the gel fraction after a heating test of heating at 120°C for 1 hour, is higher than the gel fraction before heating, which is the gel fraction before the heating test.

[0030] (17) The method for manufacturing a concentrated joint electric wire according to (16), wherein the resin curing step involves curing the curable resin by at least one curing means from heat curing, ultraviolet curing, moisture curing, and anaerobic curing.

[0031] (18) The method for manufacturing a concentrated joint electric wire according to (17), wherein the heat curing in the resin curing step is performed by heating the curable resin for a time of 80% or less of the complete heat curing time of the curable resin.

[0032] (19) A method for manufacturing a terminaled wire, wherein a metal terminal is electrically connected to a conductor portion exposed by stripping the insulating coating layer covering the end of a coated wire, the coated wire having an insulating coating layer covering the surface of the conductor, comprising: a resin coating step of coating and forming a curable resin on at least the outer surface of the exposed conductor portion of the coated wire; and a resin curing step of curing the curable resin to form a cured resin, thereby integrally forming a coating resin portion composed of the cured resin in close contact with at least the exposed conductor portion of the coated wire, wherein the resin curing step is to cure the curable resin such that the gel fraction after heating, which is the gel fraction after a heating test of heating at 120°C for 1 hour, is higher than the gel fraction before heating, which is the gel fraction before the heating test.

[0033] (20) The method for manufacturing a wire with a terminal as described in (19), wherein the resin curing step involves curing the curable resin by at least one curing means from heat curing, ultraviolet curing, moisture curing, and anaerobic curing.

[0034] (21) The method for manufacturing a wire with terminals according to (20), wherein the heat curing in the resin curing step involves heating the curable resin for a time of 80% or less of the complete heat curing time of the curable resin. [Effects of the Invention]

[0035] According to the present invention, even when a thick cured resin is present, it is possible to shorten the curing time and allow the resin deep inside to harden sufficiently due to the rise in ambient temperature after wiring, thereby improving watertightness against the penetration of moisture into the conductor portion. This also provides a method for manufacturing the same. [Brief explanation of the drawing]

[0036] [Figure 1] Figure 1 shows an example of the configuration of the end of the concentrated joint wire of the present invention, where Figure 1(a) is a cross-sectional view of the multiple insulated wires constituting the concentrated joint wire, and Figure 1(b) is a cross-sectional view when cut at the position of line II in Figure 1(a). [Figure 2] Figure 2 is a perspective view showing an example of the configuration of the end of a wire with a terminal according to the present invention. [Figure 3] Figure 3 shows an example of the configuration of the end of a terminal-equipped electric wire according to the present invention, and is a longitudinal cross-sectional view taken when the wire is cut at position P in the plane of Figure 2. [Figure 4] Figure 4 shows an example of the configuration of the end of a terminal-equipped electric wire according to the present invention, and is a cross-sectional view taken when the wire is cut at the position Q in the plane of Figure 2. [Figure 5] Figure 5 shows an example of the manufacturing method for a concentrated joint electric wire according to the present invention, where Figure 5(a) is a diagram illustrating the resin immersion process and Figure 5(b) is a diagram illustrating the resin curing process. [Figure 6] Figure 6 shows an example of the manufacturing method of the terminal-equipped electric wire of the present invention, where Figure 6(a) is a diagram illustrating the resin coating process and Figure 6(b) is a diagram illustrating the resin curing process. [Figure 7] Figure 7 is a diagram illustrating a method for evaluating the watertightness of a centralized joint electrical wire. [Modes for carrying out the invention]

[0037] The embodiments of the present invention will be described in detail below. However, the present invention is not limited to the embodiments described below, and various modifications are possible without altering the essence of the invention.

[0038] <Concentrated joint electrical wire> Figure 1 shows an example of the configuration of the end of the concentrated joint wire of the present invention. Figure 1(a) is a cross-sectional view of the multiple insulated wires constituting the concentrated joint wire, and Figure 1(b) is a cross-sectional view when cut at the position of line II in Figure 1(a). Note that the insulated wires 10a to 10g of the concentrated joint wire 1 are longitudinal, so in Figure 1(a), the insulated wires 10a to 10g are shown in cross-section.

[0039] As shown in Figures 1(a) and 1(b), the concentrated joint wire 1 is composed of a plurality of insulated wires 10a to 10g, each having conductors 11a to 11g and insulating coating layers 12a to 12g covering the conductors 11a to 11g. The insulating coating layers 12a to 12g covering each end of the plurality of insulated wires 10a to 10g are stripped to expose the conductor portion at the end, and the exposed conductor portion 14 is then bundled together and joined to form a joint 15. This concentrated joint wire 1 has a covering resin portion 18 which is composed of an inner resin portion 16 made of cured resin that is integrally formed with the joint portion 15 in close contact with at least the entire outer surface 15a of the joint portion 15, and an outer resin portion 17 that is integrally formed in close contact with at least the entire outer surface 16a of the inner resin portion 16. Of these, the cured resin has a post-heating gel fraction, which is the gel fraction after a heating test in which it is heated at 120°C for 1 hour, which is higher than the pre-heating gel fraction, which is the gel fraction before the heating test.

[0040] Thus, in the concentrated joint wire 1, which is made of a cured resin in which the inner resin portion 16 of the covering resin portion 18 that is in contact with the conductors 11a to 11g has a higher gel fraction after heating (the gel fraction after heating) than the gel fraction before heating (the gel fraction before heating), the gel fraction of the cured resin is increased in a 120°C temperature environment. Therefore, even when a large current is carried or when there are many covered wires constituting the concentrated joint wire 1, and the conductors 11a to 11g in contact with the inner resin portion 16 have thickness, the resin in the joint portion 15 and adjacent parts of the conductor portion hardens due to the rise in ambient temperature after wiring. Therefore, even when the inner resin portion 16 has a thick cured resin, it is possible to shorten the curing time for forming the concentrated joint wire 1 and to sufficiently cure the resin deep inside the inner resin portion 16 after wiring, thereby improving the watertightness (hereinafter sometimes simply referred to as "watertightness") against the intrusion of moisture into the conductor portion.

[0041] Here, the heat resistance and chemical resistance required for wire harnesses routed inside vehicles such as automobiles vary depending on the location where they are routed during vehicle installation. For example, in a wire harness routed in the engine compartment, there are locations where heat resistance and chemical resistance to windshield washer fluid at around 60°C are sufficient, locations where heat resistance and chemical resistance to automatic transmission fluid or brake fluid at around 90°C are required, and locations where heat resistance and chemical resistance to antifreeze at around 120°C are required. In conventional wire harnesses, the degree of curing of the curing resin in the covering resin part 18 (more specifically, the curing resin that constitutes the inner resin part 16 in the centralized joint wire 1, or the covering resin part 18 in the terminal-equipped wire 1A described later) was set to provide heat resistance and chemical resistance to antifreeze at 120°C, the most severe temperature environment. This resulted in the problem of a long heating time when curing the curing resin to form the covering resin part 18. In this regard, the present invention allows for the formation of a coating resin portion 18 by curing a curable resin without completely decomposing the thermal polymerization initiator, thereby forming the coating resin portion 18 to the necessary extent. This leaves room for further increasing the gel fraction and shortens the curing time required to form the coating resin portion 18. At the same time, by leaving room for further increasing the gel fraction, polymerization by the thermal polymerization initiator is restarted due to the temperature rise after wiring. As a result, the gel fraction of the cured resin is increased according to the temperature of the wiring location, and the heat resistance and chemical resistance of the cured resin in the coating resin portion 18 can be improved. Therefore, it is possible to achieve both a reduction in curing time during production and the heat resistance required when installed in a vehicle. Furthermore, in light of the current efforts to reduce greenhouse gas emissions, it is also possible to shorten the time required for the heating process in the manufacturing of the concentrated joint wire 1 (or the terminal-equipped wire 1A described later).

[0042] [Insulated wire] The concentrated joint wire 1 is composed of multiple insulated wires 10a to 10g, each having conductors 11a to 11g and insulating coating layers 12a to 12g covering the conductors 11a to 11g. Here, Figures 1(a) and 1(b) show an example with seven insulated wires 10a to 10g, but it is not limited to this. In the above-described concentrated joint wire 1, the inner resin portion 16 adjacent to the conductor portion containing the conductors 11a to 11g is made of a cured resin in which the gel fraction after heating (the gel fraction after heating, which is the gel fraction after heating at 120°C for 1 hour) is higher than the gel fraction before heating (the gel fraction before heating). As a result, the entire inner resin portion 16 hardens sufficiently due to the temperature rise around the concentrated joint wire 1 after wiring, so that even if there are many insulated wires constituting the concentrated joint wire 1, the resin deep inside the conductor portion can also harden.

[0043] Here, examples of materials for the metal strands constituting the conductors 11a to 11g of the insulated electric wires 10a to 10g include copper, copper alloys, aluminum, aluminum alloys, and materials to which these materials have various platings. The metal strands constituting the conductors 11a to 11g may be made of a single metal wire, or they may be made of multiple metal wires twisted together. Furthermore, the metal strands constituting the conductors 11a to 11g may be fiber electric wires in which metals such as copper or tin are coated onto fibers, or they may be electric wires reinforced with fibers as tension members by twisting and winding metal wires around the fibers.

[0044] Furthermore, examples of materials for the insulating coating layers 12a to 12g of the insulated wires 10a to 10g include polyvinyl chloride, rubber, polyolefin, and thermoplastic elastomer. These may be used individually or in mixtures of two or more. Various additives may be added to the insulating coating layers 12a to 12g as appropriate. Examples of additives include flame retardants, fillers, and colorants.

[0045] The number of insulated wires constituting the concentrated joint wire 1 is preferably in the range of 2 to 20, and more preferably in the range of 2 to 10. If the number of insulated wires is large, the thickness of the inner resin portion 16 will be larger, but even in that case, the resin in the deeper parts hidden by the insulated wires can be sufficiently cured.

[0046] These insulated wires 10a to 10g have a joint 15 formed by stripping the insulating coating layers 12a to 12g covering their ends, exposing the conductor portion at the end, and then bundling and joining the exposed conductor portion 14. At this time, in the exposed conductor portion 14 of the insulated wires 10a to 10g, the conductors 11a to 11g are exposed and not covered by the insulating coating layers 12a to 12g. By joining and integrating the exposed conductor portion 14 of the exposed conductors 11a to 11g to form the joint 15, the conductors 11a to 11g become electrically conductive to each other.

[0047] The joint 15 of the insulated wires 10a to 10g may be formed by known joining methods such as crimping (fumigation crimping) or welding.

[0048] In the insulated wires 10a to 10g, the conductors 11a to 11g located at the exposed conductor portion 14 are bundled together. In this case, the conductors 11a to 11g may be twisted together at least partially. When the conductors 11a to 11g are bundled in this way, it is often difficult to harden the inner resin portion 16 in the gaps between the conductors 11a to 11g. However, since the entire inner resin portion 16 is further hardened by the temperature rise around the concentrated joint wire 1 after wiring, a wider portion of the inner resin portion 16, including the gaps between the conductors 11a to 11g, can be sufficiently hardened after wiring.

[0049] [Coated resin part] The concentrated joint wire 1 has a covering resin portion 18 which is composed of an inner resin portion 16 and an outer resin portion 17.

[0050] Of these, the inner resin portion 16 is a portion made of cured resin that is integrally formed with the joint portion 15 in a state of close contact over at least the entire outer surface 15a of the joint portion 15. Such a cured resin is made up of cured material of a curable resin, and before curing, the curable resin has the property of easily penetrating into the gaps between the conductors 11a to 11g and into the irregularities on the surface of the conductors 11a to 11g.

[0051] Here, the inner resin portion 16 is more preferably formed in close contact with at least the entire outer surface of the conductors 11a to 11g, in addition to the outer peripheral surface 15a of the joint 15, from the viewpoint of further preventing water, electrolyte, etc. that have penetrated inside the insulating coating layers 12a to 12g from penetrating to other circuits through the joint 15, and even more preferably formed in close contact with the entire outer surface of the conductors 11a to 11g and the outer surface of the portion of the insulating coating layers 12a to 12g adjacent to the conductors 11a to 11g.

[0052] The cured resin constituting the inner resin portion 16 has a higher gel fraction after heating (hereinafter sometimes simply referred to as "post-heating gel fraction") than the gel fraction before heating (hereinafter sometimes simply referred to as "pre-heating gel fraction"), which is the gel fraction after a heating test in which it is heated at 120°C for 1 hour. As a result, the curing of the inner resin portion 16 progresses further due to the temperature rise around the concentrated joint electric wire 1 after wiring, and the resin deep inside the conductor portion is sufficiently cured, thereby improving watertightness.

[0053] Here, it is preferable that the gel fraction of the cured resin constituting the inner resin portion 16 after heating is 12.5% ​​or more higher than the gel fraction before heating. This allows the cured resin to further harden in a shorter time due to the temperature rise around the concentrated joint wire 1 after wiring, and further enhances the heat resistance and chemical resistance to windshield washer fluid at around 60°C.

[0054] In particular, it is more preferable that the gel fraction of the cured resin constituting the inner resin portion 16 after heating is 25.0% or more higher than the gel fraction before heating. This allows the curing of the cured resin to proceed further in a shorter time due to the temperature rise around the concentrated joint wire 1 after routing, and further enhances the heat resistance and chemical resistance to automatic transmission fluid and brake fluid at around 90°C.

[0055] Furthermore, it is particularly preferable that the gel fraction of the cured resin constituting the inner resin portion 16 after heating is 50.0% or more higher than the gel fraction before heating. This allows the cured resin to further harden in a shorter time due to the temperature rise around the concentrated joint wire 1 after wiring, and further enhances the heat resistance and chemical resistance to antifreeze at around 120°C.

[0056] The cured resin constituting the inner resin portion 16 is exposed to heat appropriate to the environment in which these heated chemicals are present. This allows the thermal polymerization initiator remaining in the cured resin to rapidly promote further polymerization of the cured resin, thereby increasing the degree of crosslinking (gel fraction) of the cured resin to a degree of crosslinking appropriate to the environment in which each chemical is present. As a result, the cured resin can be made to have the desired heat resistance and chemical resistance.

[0057] On the other hand, the upper limit of the difference between the gel fraction after heating and the gel fraction before heating in the cured resin constituting the inner resin portion 16 is not particularly limited, but it may be set to 60%, for example, from the viewpoint of maintaining the strength of the wires and terminals of the cured resin before heating.

[0058] The curable resin used in the inner resin portion 16 contains at least (meth)acrylate monomer and a reactive diluent as curable components. In addition, the curable resin used in the inner resin portion 16 contains at least a polymerization initiator in addition to the curable components.

[0059] Here, known (meth)acrylate monomers such as epoxy (meth)acrylate, polyester acrylate, urethane (meth)acrylate, silicone (meth)acrylate, and amine-modified acrylate can be used. Among these, one or more of epoxy (meth)acrylate, polyester acrylate, urethane (meth)acrylate, silicone (meth)acrylate, and amine-modified acrylate, which have an acrylate group or methacrylate group at the terminal and whose linear portion is composed of one or more of polyurethane, polyether, and polysiloxane, are preferred because they have a significant effect in further increasing the degree of deep crosslinking (gel fraction) when heated to cured resin.

[0060] Furthermore, the reactive diluent contains one or more monofunctional monomers that can be polymerized using the polymerization initiator described later, and one or more selected from isoamyl acrylate, lauryl acrylate, isostearyl acrylate, stearyl acrylate, isobornyl acrylate, acryloyl morpholine, phenoxyethyl acrylate, phenoxydiethylene glycol acrylate, phenoxypolyethylene glycol acrylate, ethoxydiethylene glycol acrylate, methoxytriethylene glycol acrylate, methoxypolyethylene glycol acrylate, methoxydipropylene glycol acrylate, 2-hydroxyethyl acrylate, 2-hydroxypropyl acrylate, dipropylene glycol acrylate, 2-acryloyloxyethyl succinic acid, 2-acryloyloxyethyl hexahydrophthalic acid, and 2-acryloyloxyethyl phthalate can be used.

[0061] Furthermore, the polymerization initiator includes at least a thermal polymerization initiator consisting of a known substance that initiates the polymerization of oligomers and reactive diluents by heat. In this case, the cured resin is preferably a thermosetting resin. This allows the degree of crosslinking (gel fraction) of the cured resin to increase due to the rise in ambient temperature after application, thereby further curing and improving the heat resistance and chemical resistance of the cured resin. In addition, if no other substances are included as polymerization initiators, a portion of the thermal polymerization initiator can be used to polymerize oligomers and reactive diluents, thereby curing the curable resin and forming a cured resin.

[0062] In particular, it is preferable to use a thermal radical polymerization initiator that has the effect of initiating radical polymerization by heat. Conventional known thermal radical polymerization initiators can be used, for example, compounds that have an -OO- bond in their molecule and readily generate free radicals upon heating, react with the double bonds at the molecular ends of acrylate monomers, etc., and initiate radical polymerization in a chain reaction.

[0063] Examples of thermal radical polymerization initiators include ketone peroxides, peroxyketals, hydroperoxides, dialkyl peroxides, diacyl peroxides, peroxyesters, and peroxydicarbonates, and one or more of these can be used in combination. The half-life temperature range for thermal radical polymerization initiators is, for example, between 90°C and 180°C.

[0064] Here, the "1-minute half-life temperature" of a thermal radical polymerization initiator is the temperature at which half (50%) of the thermal radical polymerization initiator decomposes in one minute. This temperature is determined by the type of thermal radical polymerization initiator and is independent of the concentration (amount used) of the thermal radical polymerization initiator. By placing a thermal radical polymerization initiator at this "1-minute half-life temperature," the amount of thermal radical polymerization initiator is halved every minute, and 99.9% of the thermal radical polymerization initiator decomposes in 10 minutes. Therefore, the "1-minute half-life temperature" of a thermal radical polymerization initiator serves as a guideline for polymerization conditions when polymerizing a curable resin containing a thermal radical polymerization initiator.

[0065] The content of the thermal radical polymerization initiator is preferably in the range of 0.1 parts by mass or more and 2.0 parts by mass or less per 100 parts by mass of the curable component of the curable resin. If the content of the thermal radical polymerization initiator is less than 0.1 parts by mass, it will not be a sufficient amount to further increase the gel fraction of the curable resin. On the other hand, if the content of the thermal radical polymerization initiator exceeds 2.0 parts by mass, the gel fraction of the curable resin will increase excessively due to the rise in temperature around the concentrated joint wire 1 after wiring, resulting in an excessive crosslinking density and causing cracks in the curable resin, thus reducing the water-sealing ability of the curable resin.

[0066] When using a thermal polymerization initiator as the polymerization initiator, it is desirable that the heating time of the curable resin at the start of polymerization be in the range of 30 seconds to 120 seconds. If the heating time of the curable resin is less than 30 seconds, the thermal conductivity of the curable resin is low, so it will not heat sufficiently and the curing of the curable resin will not proceed easily. On the other hand, if the heating time of the curable resin exceeds 120 seconds, the efficiency of the heating process for the curable resin will decrease in the manufacturing process. In particular, if this heating time of the curable resin is shorter than the time it takes for the substantially entire amount of thermal polymerization initiator to be consumed (for example, 10 times the half-life), the heating time for forming the curable resin can be shortened, and since the resulting curable resin contains the thermal polymerization initiator, the curable resin can be further cured by the temperature rise around the concentrated joint wire 1 after wiring, thereby improving the watertightness of the curable resin.

[0067] On the other hand, the polymerization initiator may include, in addition to a thermal polymerization initiator, a substance that initiates polymerization of oligomers and reactive diluents by ultraviolet light or moisture, or a substance that initiates polymerization of oligomers and reactive diluents by contact with a metal in the absence of oxygen. In this case, it is preferable that the cured resin further has one or more curability properties from ultraviolet curability, moisture curability, and anaerobic curability. As a result, the oligomers and reactive diluents polymerize by ultraviolet light, moisture, or contact with a metal, so that the curable resin can be cured to form a cured resin while conserving the thermal polymerization initiator to further increase the degree of crosslinking of the cured resin. Among these substances, it is more preferable to use an ultraviolet polymerization initiator that initiates polymerization by irradiation with ultraviolet light. In this case, it is even more preferable that the cured resin further has ultraviolet curability.

[0068] The UV polymerization initiator is not particularly limited as long as it is a compound that absorbs ultraviolet light and initiates radical polymerization; conventionally known ones can be used. Examples of UV polymerization initiators include azo compounds, benzoin-based, benzophenone-based, alkylphenone-based, acylphosphine oxide-based, oxime ester-based, anthraquinone-based, and thioxanthone-based UV polymerization initiators. Among these, examples of alkylphenone-based UV polymerization initiators include benzyldimethyl ketal, α-hydroxyalkylphenone, and α-aminoalkylphenone, and one or more of these can be used in combination.

[0069] The appropriate amount of UV polymerization initiator can be determined by experimentation, but for example, the UV polymerization initiator is preferably in the range of 0.5 parts by mass or more and 3.0 parts by mass or less per 100 parts by mass of the curable component of the curable resin. If the UV polymerization initiator content is less than 0.5 parts by mass per 100 parts by mass of the curable component of the curable resin, the amount of radicals generated by the UV polymerization initiator absorbing ultraviolet light will be small, which may result in insufficient curing of the curable resin by ultraviolet light. On the other hand, if the UV polymerization initiator content exceeds 3.0 parts by mass per 100 parts by mass of the curable component of the curable resin, when forming a curable resin with a large thickness, the amount of ultraviolet light absorbed by the UV polymerization initiator will increase, which may result in a decrease in the deep curing properties of the curable resin.

[0070] When using an ultraviolet polymerization initiator as the polymerization initiator, the ultraviolet light irradiated to initiate radical polymerization can have a wavelength of less than 400 nm, and as an example, a UV-LED with a wavelength of 365 nm can be used. The irradiation intensity of the ultraviolet light to initiate radical polymerization can be, for example, 100 mW / cm². 2 More than 1000mW / cm 2 The following ranges are possible. Furthermore, the UV irradiation time for initiating radical polymerization can be in the range of 1 second to 30 seconds. UV irradiation may be repeated, for example, 2 to 10 times, for durations ranging from 1 second to 30 seconds.

[0071] In particular, when using a combination of a thermal radical polymerization initiator and an ultraviolet polymerization initiator as polymerization initiators, it is preferable to cure the curable resin by irradiation with ultraviolet light first, and then further cure the curable resin by heating, in order to increase the difference in gel fraction before and after a heating test at 120°C for 1 hour. Here, it is preferable to set the heating temperature and time when further curing the curable resin by heating according to the 1-minute half-life temperature of the thermal radical polymerization initiator. For example, when using 2,5-dimethyl-2,5-di-(2-ethylhexanoylperoxy)hexane (manufactured by NOF Corporation, product name: Perhexa 250), which has a 1-minute half-life temperature of 118.8°C, as the thermal radical polymerization initiator, heating at 120°C allows the difference in gel fraction before and after a heating test at 120°C for 1 hour to be controlled to 12.5% ​​or more, 25.0% or more, or 50.0% or more, depending on the heating time.

[0072] The content of polymerization initiators in the inner resin portion 16 can be identified using general chemical analysis techniques for additives in polymers, and these techniques have been disclosed by Toray Research Center, Inc. and others.

[0073] One specific method involves first performing a qualitative analysis of each additive to identify the type of compound, then preparing compositional samples with varying amounts of the identified compound added to the resin and performing chemical analysis (quantitative analysis) on them, creating a calibration curve that shows the relationship between the amount added and the amount detected from the quantitative analysis, and then applying the amount detected from the quantitative analysis of the inner resin portion 16 to the calibration curve to estimate the polymerization initiator content in the inner resin portion 16.

[0074] Here, known methods can be used for qualitative and quantitative analysis. For qualitative analysis, for example, the polymerization initiator can be extracted from the inner resin portion 16 using a solvent, and then, for example, high-resolution LC / ESIMS analysis can be performed to qualitatively analyze each additive. LC (liquid chromatography) analysis is classified as a type of high-performance liquid chromatography (HPLC) and is a method that separates components in a liquid using the difference in interaction between the stationary phase and the mobile phase. LC / ESIMS analysis is a method that connects ESIMS (electrospray ionization mass spectrometry) to LC analysis, ionizes each separated substance, estimates its molecular weight from its spectrum, and identifies the substance. Furthermore, LC / MS / MS is preferably used for quantitative analysis. The method of connecting a mass detector to the above-mentioned LC analysis and detecting only specific masses by fragmentation is called LC / MS / MS. Because LC / MS / MS is less affected by other coexisting substances, it is a method that enables highly selective analysis.

[0075] In addition to the curing components and polymerization initiators mentioned above, this curable resin may also contain antioxidants, sensitizers, anti-aging agents, etc., as needed.

[0076] Among these, antioxidants are not particularly limited, but examples include amine antioxidants, phenol antioxidants, or sulfur antioxidants. Examples of amine antioxidants include polymers of 4,4'-dioctyldiphenylamine, N,N'-diphenyl-p-phenylenediamine, and 2,2,4-trimethyl-1,2-dihydroquinoline. Examples of phenol antioxidants include 2,4-dimethyl-6-(1-methylpentadecyl)phenol, pentaerythritol-tetrakis(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate), octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, and 1,3,5-trimethyl-2,4,6-tris(3,5-di-tert-butyl-4-hydroxybenzyl)benzene. Examples of sulfur antioxidants include bis(2-methyl-4-(3-n-alkylthiopropionyloxy)-5-tert-butylphenyl) sulfide, 2-mercaptobenzimidazole and its zinc salt, and pentaerythritol-tetrakis(3-lauryl-thiopropionate).

[0077] Furthermore, sensitizers are compounds that generate free radical species and induce a chain reaction when light is used to photopolymerize (meth)acrylate monomers, and examples include coumarin, pyrazoline, thiophene, naphthalene, and oxazole. Among these, compounds with absorbers in the same wavelength range as the irradiated ultraviolet light wavelength of 365 nm, such as coumarin, thiophene, and oxazar, are more preferable because they have a high absorption rate of ultraviolet light and efficiently generate free radical species and cationic species to induce a chain reaction.

[0078] The inner resin portion 16 of the concentrated joint wire 1 preferably has a thickness in the range of 3.0 mm to 15.0 mm. In this case, the thickness t of the cured resin constituting the inner resin portion 16 is in the range of 3.0 mm to 15.0 mm. When curing the curable resin using ultraviolet light, if the ultraviolet light used for further curing the curable resin has a transmission distance of 15.0 mm or less, it can penetrate the interior of the curable resin and contribute to the formation of the cured resin by curing the curable resin within that range. Therefore, by setting the thickness t of the cured resin constituting the inner resin portion 16 to the range of 3.0 mm to 15.0 mm, it is possible to further cure the curable resin using ultraviolet light. In particular, even when the outer diameter of the conductors 11a to 11g is large and the thickness t of the cured resin constituting the inner resin portion 16 is large, this concentrated joint wire 1 shortens the curing time required to cure the curable resin and obtain the cured resin. Furthermore, the temperature rise around the concentrated joint wire 1 after wiring allows the cured resin to further harden sufficiently in the deeper parts of the inner resin portion 16 (i.e., near the conductors 11), thereby improving the watertightness provided by the cured resin.

[0079] Here, the thickness t of the cured resin constituting the inner resin portion 16 can be determined by cutting a cross section from the concentrated joint wire 1 along the thickness direction of the cured resin, polishing the resulting cross section to make it smooth, observing the smoothed cross section with a microscope or the like, and measuring the thickness using the microscope's measurement function, and this thickness is equal to the thickness of the curable resin before curing. In this case, the location where the thickness t of the inner resin portion 16 is measured can be, for example, the thickness of the location where the conductors 11a to 11g are exposed.

[0080] On the other hand, the outer resin portion 17 is a portion that is integrally formed in close contact with at least the entire outer circumferential surface 16a of the inner resin portion 16. Since the concentrated joint wire 1 has an outer resin portion 17 and an inner resin portion 16 as the covering resin portion 18, the outer resin portion 17 and the inner resin portion 16 have a double structure, which can improve watertightness against the intrusion of moisture from the outside of the covering resin portion 18, thereby further improving watertightness by the cured resin.

[0081] Here, it is preferable that the outer resin portion 17 is a resin container that houses and holds at least the joint portion 15 and the inner resin portion 16 inside. This allows the curable resin that will become the inner resin portion 16 and the joint portion 15 to be housed in the resin container which is the outer resin portion 17, and the curable resin to be cured to form the inner resin portion 16. As a result, the covering resin portion 18 can be formed efficiently, and the bonding strength between the outer resin portion 17 and the inner resin portion 16 can be increased.

[0082] When using an ultraviolet polymerization initiator as described above, it is preferable that the outer resin portion 17 be made of a resin that transmits ultraviolet light. More specifically, when the curable resin used in the inner resin portion 16 is an ultraviolet curable resin, it is even more preferable that the resin container used in the outer resin portion 17 is a resin container that transmits ultraviolet light. This allows the curable resin to be cured using ultraviolet light while the curable resin is held in the outer resin portion 17, thus further shortening the time required to form a cured resin from a curable resin.

[0083] Specific examples of resins that transmit ultraviolet light among the outer resin portion 17 include polypropylene, polyethylene, polyamide, polyvinyl alcohol, polyethylene terephthalate, polyvinyl chloride, polyvinylidene chloride, and polystyrene. Here, the polyamide is preferably a transparent polyamide. Furthermore, the polyvinyl chloride is preferably one with a plasticizer content of 20% by mass or less, and more preferably one that does not contain a plasticizer. As such a resin that transmits ultraviolet light, it is preferable to use a resin with a transmittance of 60% or more for ultraviolet light at a wavelength of 365 nm, and among these, it is more preferable to use a resin that transmits light in the visible range (wavelength 400 to 700 nm). In particular, by using a transparent resin that has a transmittance of 60% or more for ultraviolet light at a wavelength of 365 nm and transmits light in the visible range, the cured portion can be visually inspected when curing the curable resin to form the inner resin portion 16, thereby improving the workability when curing the curable resin.

[0084] The thickness t' of the outer resin portion 17 is preferably in the range of 0.3 mm to 3.0 mm. If the thickness t' of the outer resin portion 17 is less than 0.3 mm, the mechanical strength of the outer resin portion 17 decreases, making it prone to breakage due to shrinkage stress when curing the curable resin held inside the outer resin portion 17 to form the inner resin portion 16. On the other hand, if the thickness t' of the outer resin portion 17 exceeds 3.0 mm, the transmittance of electromagnetic waves such as ultraviolet rays of the outer resin portion 17 itself decreases, which may reduce the curability of the curable resin held inside the outer resin portion 17. Therefore, from the viewpoint of facilitating the formation of the inner resin portion 16 by curing the curable resin held inside the outer resin portion 17, the thickness t' of the outer resin portion 17 is preferably in the range of 0.3 mm to 3.0 mm, and more preferably in the range of 0.5 mm to 2.0 mm. Here, the thickness t' of the outer resin portion 17 can be the average thickness of the outer resin portion 17 when viewed in a cross-section perpendicular to the extension direction of the conductors 11a to 11g.

[0085] [Applications of concentrated jointed electrical wires] As described above, the concentrated joint wire 1 has excellent watertightness and can therefore be suitably used in wire harnesses routed in vehicles such as automobiles. Here, the wire harness consists of a bundle of multiple insulated wires, including the concentrated joint wire 1 described above. In the wire harness, some of the multiple insulated wires may constitute the concentrated joint wire 1, or all of them may constitute the concentrated joint wire 1.

[0086] The wire harness may be bundled with tape, or it may be covered with an outer covering such as a round tube, corrugated tube, or protector. In this case, it is preferable that some or all of the multiple insulated wires 10a to 10g that make up the centralized joint wire 1 are bundled or covered outside the insulated resin part 18. This at least partially fixes the positional relationship of the insulated wires 10a to 10g that are pulled out to the outside of the insulated resin part 18, thereby further increasing the durability of the centralized joint wire 1.

[0087] <Electric wire with terminals> Figure 2 is a perspective view showing an example of the configuration of the end of a terminal-equipped wire according to the present invention. Figure 3 is a diagram showing an example of the configuration of the end of a terminal-equipped wire according to the present invention, and is a longitudinal cross-sectional view taken when the wire is cut at position P in the plane of Figure 2. Figure 4 is a diagram showing an example of the configuration of the end of a terminal-equipped wire according to the present invention, and is a transverse cross-sectional view taken when the wire is cut at position Q in the plane of Figure 2. In the following description and in Figures 2 to 4, the same reference numerals are used for the components that are the same as the components of the concentrated joint wire shown in Figure 1. In the perspective view of Figure 2, the coating resin part 18A is shown as a dotted line because it shows the components inside the coating resin part 18A.

[0088] As shown in Figures 2 to 4, the terminal-equipped wire 1A comprises a coated wire 10 in which an insulating coating layer 12 is covered on the surface of a conductor 11, and a metal terminal 20 that is electrically connected to the portion of the conductor 11 that is exposed by stripping the insulating coating layer 12 covering the end of the coated wire 10. In this terminal-equipped wire 1A, a coating resin portion 18A made of cured resin is formed on the outer surface of at least the exposed conductor portion of the coated wire 10, and the gel fraction after heating, which is the gel fraction after a heating test in which the resin is heated at 120°C for 1 hour, is higher than the gel fraction before heating, which is the gel fraction before the heating test.

[0089] Thus, in a terminal-equipped electric wire 1A, the gel fraction after heating (the gel fraction after a heating test of 120°C for 1 hour) of the cured resin coating part 18A that is in contact with the conductor is higher than the gel fraction before heating (the gel fraction before the heating test). Since the gel fraction of the cured resin is increased in a 120°C temperature environment, even when a large current is carried or when there are many coated wires constituting the concentrated joint electric wire 1, and the portion of the conductor 11 in contact with the coating part 18A is thick, the resin in the parts of the conductor that are in shadow of the conductor 11, which are deep within the conductor portion, hardens due to the rise in ambient temperature after wiring. Therefore, even when the coating part 18A has a thick cured resin, it is possible to shorten the curing time for forming the terminal-equipped electric wire 1A and to sufficiently harden the resin deep within the coating part 18 after wiring, thereby providing a terminal-equipped electric wire 1A that can improve watertightness against the intrusion of moisture into the conductor portion.

[0090] As shown in Figures 2 and 3, the terminal-equipped wire 1A comprises at least a coated wire 10 and a metal terminal 20.

[0091] [Insulated wire] In this case, the insulated wire 10 has an insulating coating layer 12 covering the surface of the conductor 11. The aforementioned wire with terminals 1A is made of a cured resin in which the gel fraction after heating (the gel fraction after heating, which is the gel fraction after heating at 120°C for 1 hour) is higher than the gel fraction before heating (the gel fraction before heating), which is the gel fraction before heating, in the conductor portion containing the conductor and the adjacent coating resin portion 18A. As a result, the resin deep within the coating resin portion 18A can be sufficiently cured by the temperature rise around the wire with terminals 1A after it has been wired.

[0092] Here, as examples of materials for the metal strands constituting the conductor 11 of the insulated wire 10, similar to the conductors 11a to 11g described above, examples include copper, copper alloys, aluminum, aluminum alloys, and materials to which these materials have various platings. Furthermore, the metal strands constituting the conductor 11 may be fiber wires in which metals such as copper or tin are coated onto fibers, or they may be wires reinforced with fibers as tension members by twisting and winding metal wires around the fibers. The metal strands constituting the conductor 11 may be made of a single metal wire, but it is preferable that they be made of multiple metal wires twisted together to facilitate the crimping of the metal terminal 20 described later.

[0093] Furthermore, as for the insulating coating layer 12 of the insulated wire 10, examples of materials include polyvinyl chloride, rubber, polyolefin, thermoplastic elastomer, etc., similar to the insulating coating layers 12a to 12g described above. These may be used individually or in mixtures of two or more. Here, various additives may be added to the insulating coating layer 12 as appropriate.

[0094] [Metal terminal] The metal terminal 20 is electrically connected to the conductor portion exposed by stripping the insulating coating layer 12 covering the end of the insulated wire 10. By connecting the metal terminal 20 to this exposed portion of the conductor 11, the metal terminal 20 and the conductor 11 become electrically connected to each other.

[0095] The metal terminal 20 is of the open barrel type and is made of, for example, copper or a copper alloy. As shown in Figures 2 and 3, the metal terminal 20 is constructed by connecting the terminal body (wire barrel) 21, the conductor crimping section 23, and the insulation crimping section (insulation barrel) 25 via a transition section 22. The transition section 22, located between the conductor crimping section 23 and the insulation crimping section 25 and the terminal body 21, has an opening at the top.

[0096] The terminal body 21 is formed from a plate-like material of a predetermined shape into a cylindrical shape with a rectangular cross-section. Furthermore, as shown in Figure 3, the terminal body 21 may have an elastic contact piece 26 inside, formed by folding the plate-like material into the rectangular cylindrical body. This terminal body 21 is connected by inserting a male terminal or the like from its front end (the left end in Figure 3). In the following description, an example is shown where the terminal body 21 is a female terminal that allows the insertion of an insertion tab (not shown) for a male terminal or the like. However, in this invention, the shape of the details of this terminal body 21 is not particularly limited. For example, instead of a female terminal body 21, it may have an insertion tab for a male terminal.

[0097] The conductor crimping portion 23 and the insulation crimping portion 25 are the parts that are crimped to the insulated wire 10. Before crimping, the metal terminal 20 has a barrel shape with a cross-sectional shape that is approximately U-shaped, perpendicular to the longitudinal direction (left-right direction in Figure 3). The metal terminal 20 has a conductor crimping portion 23 that crimps the conductor 11 exposed from the insulating coating layer 12 to the tip side of the insulated wire 10, an insulation crimping portion 25 that crimps the insulating coating layer 12 of the insulated wire 10, and a barrel section 24 formed by the opening between the conductor crimping portion 23 and the insulation crimping portion 25.

[0098] At the tip of the insulated wire 10, the insulating coating layer 12 has been peeled off, exposing the internal conductor 11. The insulating coating layer 12 of the insulated wire 10 is crimped by the coating crimping portion 25 of the metal terminal 20. The conductor 11, which is exposed after the insulating coating layer 12 has been peeled off, is crimped by the conductor crimping portion 23. At the conductor crimping portion 23, the conductor 11 and the metal terminal 20 are electrically connected. The end face of the insulating coating layer 12 is located in the barrel section 24 between the coating crimping portion 25 and the conductor crimping portion 23.

[0099] [Coated resin part] As shown in Figure 3, the terminal-equipped wire 1A has a coating resin portion 18A made of hardened resin formed on the outer surface of at least the exposed conductor 11 portion of the insulated wire 10.

[0100] This covering resin portion 18A is a portion made of cured resin that is integrally formed with the conductor 11 in close contact with the exposed portion of the conductor 11 from at least the barrel-to-barrel portion 24 to the wire crimping portion 23. Here, the conductor 11 is not exposed to the outside by the covering resin portion 18A. Such a cured resin is made of a cured product of a curable resin similar to the inner resin portion 16 described above, and the curable resin before curing has the property of easily penetrating into the gap between the conductor 11 and the metal terminal 20, and into the irregularities on the surface of the conductor 11.

[0101] Here, in order to further prevent water, electrolyte, etc. from penetrating the conductor 11 and thereby further enhance the water-sealing properties of the coating resin portion 18A, it is preferable that the coating resin portion 18A is formed in close contact with one or both of the following: the entire outer surface of the conductor 11, the outer surface of the portion of the metal terminal 20 adjacent to the conductor 11, and the outer surface of the portion of the insulating coating layer 12 adjacent to the conductor 11.

[0102] The coating resin portion 18A can be made of the same curing resin used in the inner resin portion 16 described above. That is, the curing resin constituting the coating resin portion 18A has the characteristic that the gel fraction after heating, which is the gel fraction after a heating test of heating at 120°C for 1 hour, is higher than the gel fraction before heating, which is the gel fraction before the heating test. As a result, the curing of the coating resin portion 18A progresses further due to the temperature rise around the terminal-equipped electric wire 1A after wiring, and the resin deep inside the conductor portion is sufficiently cured, thereby improving watertightness. Therefore, the coating resin portion 18A can also function as, for example, a corrosion-resistant layer.

[0103] Here, it is preferable that the gel fraction of the cured resin constituting the coating resin portion 18A after heating is 12.5% ​​or more higher than the gel fraction before heating. This allows the cured resin to further harden in a shorter time due to the temperature rise around the terminal-equipped wire 1A after routing, and further enhances the heat resistance and chemical resistance to windshield washer fluid at around 60°C.

[0104] In particular, it is more preferable that the gel fraction of the cured resin constituting the coating resin portion 18A after heating is 25.0% or more higher than the gel fraction before heating. This allows the curing of the cured resin to proceed further in a shorter time due to the temperature rise around the terminal-equipped electric wire 1A after routing, and further enhances the heat resistance and chemical resistance to automatic transmission fluid and brake fluid at around 90°C.

[0105] Furthermore, it is particularly preferable that the gel fraction of the cured resin constituting the coating resin portion 18A after heating is 50.0% or more higher than the gel fraction before heating. This allows the curing of the cured resin to proceed further in a shorter time due to the temperature rise around the terminal-equipped electric wire 1A after routing, and further enhances the heat resistance and chemical resistance to antifreeze at around 120°C.

[0106] On the other hand, the upper limit of the difference between the gel fraction after heating and the gel fraction before heating in the cured resin constituting the coating resin portion 18A is not particularly limited, but it may be set to 60%, for example, from the viewpoint of maintaining the strength of the wires and terminals of the cured resin before heating.

[0107] The curable resin used in the coating resin portion 18A contains at least (meth)acrylate monomer and a reactive diluent as curable components. In addition, the curable resin used in the coating resin portion 18A contains at least a polymerization initiator in addition to the curable components. Since the curable resin used in the coating resin portion 18A can be composed of the same curable resin as the curable resin used in the inner resin portion 16 described above, a detailed description of the composition of the curable resin will not be repeated.

[0108] The curable resin used in the coating resin portion 18A contains at least a thermal polymerization initiator, which is a known substance that initiates the polymerization of oligomers and reactive diluents by heat. In this case, the curable resin is preferably a thermosetting resin.

[0109] On the other hand, the polymerization initiator may include, in addition to a thermal polymerization initiator, a substance that initiates the polymerization of oligomers and reactive diluents by ultraviolet light or moisture, or a substance that initiates the polymerization of oligomers and reactive diluents by contact with a metal in the absence of oxygen. In this case, it is preferable that the cured resin further has one or more curability properties from ultraviolet curability, moisture curability, and anaerobic curability.

[0110] Since at least a portion of the covering resin portion 18A is located inside the metal terminal 20 and outside the conductor 11, it is preferable that at least a portion of it exists in the gap between the metal terminal 20 and the conductor 11. When forming the covering resin portion 18A, if a curable resin is applied to the portion of the barrel space 24 between the terminal body 21 and the conductor crimping portion 23 of the terminal-equipped wire 1A where the conductor 11 is exposed, a portion of the curable resin penetrates into the void inside the conductor 11. In addition, the curable resin applied to the barrel space 24 penetrates into the gap between the inner wall 20a of the metal terminal 20 and the conductor 11, reaching the gap between the bottom 20c of the metal terminal 20 and the conductor 11. In this case, the conductor 11 casts a shadow over the curable resin that has penetrated the voids inside the conductor 11 and the curable resin that has penetrated the gap between the inner wall 20a of the metal terminal 20 and the conductor 11. Therefore, when ultraviolet light is irradiated, it is desirable to make it easier for ultraviolet light to reach the curable resin constituting the coating resin portion 18A, thereby making curing defects in the curable resin less likely to occur.

[0111] In this terminal-equipped electric wire 1A, from the viewpoint of allowing ultraviolet light to reach the part of the conductor 11 that is in shadow, it is preferable that the length of the portion of the covering resin 18A that faces the area from the end 20b to the bottom 20c of the inner wall 20a of the metal terminal 20 is in the range of 3.0 mm to 15.0 mm. More specifically, when the wire is cut perpendicular to the extending direction X of the conductor 11 at the position of the plane Q crossing the opening of the barrel-interval portion 24 shown in Figure 2, and viewed in the cross-section shown in Figure 4, it is preferable that the length L of the contour formed by the inner wall 20a of the metal terminal 20 in the barrel-interval portion 24, from the end 20b to the bottom 20c of the metal terminal 20, is in the range of 3.0 mm to 15.0 mm. When further curing the curable resin using ultraviolet light, as described above, if the ultraviolet light used for further curing the curable resin has a transmission distance of 15.0 mm or less, it can penetrate the interior of the curable resin and contribute to the formation of the cured resin by curing the curable resin within that range. Ultraviolet light used for further curing the curable resin enters from near the end 20b of the metal terminal 20, reflects between the inner wall 20a of the metal terminal 20 and the outer surface of the conductor 11, and reaches the bottom 20c of the metal terminal 20. Therefore, by setting the length L from the end 20b to the bottom 20c of the metal terminal 20 to a range of 3.0 mm to 15.0 mm, further curing of the curable resin using ultraviolet light can be facilitated. Even when the outer diameter of the conductor 11 is large, this terminal-equipped wire 1A shortens the curing time required to cure the curable resin and obtain the cured resin. Furthermore, the temperature rise around the terminal-equipped wire 1A after wiring allows the cured resin to further sufficiently harden even the resin in the deeper parts of the coating resin portion 18A that is in the shadow of the conductor 11 (i.e., near the bottom 20c of the metal terminal 20), thereby improving the watertightness provided by the cured resin.

[0112] Here, the length L of the portion of the terminal-equipped wire 1A that faces the inner wall 20a of the metal terminal 20 from its end 20b to its bottom 20c can be measured by cutting out a cross section (for example, the cross section shown in Figure 4) perpendicular to the extending direction X of the conductor 11 of the terminal-equipped wire 1A at the position of the plane Q that crosses the opening of the barrel section 24 in Figure 2, polishing the obtained cross section to make it smooth, observing the smoothed cross section with a microscope, and measuring it using the measurement function of the microscope. Here, the position of the bottom 20c of the inner wall 20a of the metal terminal 20 can be, for example, a position where the length to both ends 20b, 20b of the inner wall 20a is equal. In this case, the covering resin portion 18A may be configured such that half of the length facing the inner wall 20a of the metal terminal 20 is in the range of 3.0 mm to 15.0 mm.

[0113] [Applications of wires with terminals] As described above, the terminal-equipped wire 1A has excellent watertightness and can therefore be suitably used in wire harnesses routed in vehicles such as automobiles, similar to the centralized joint wire 1. Here, a wire harness may be configured that includes one or both of the above-described centralized joint wire and the terminal-equipped wire.

[0114] <Manufacturing method for concentrated jointed electric wires> Figure 5 shows an example of a manufacturing method for a concentrated joint electric wire according to the present invention. Figure 5(a) is a diagram illustrating the resin immersion process, and Figure 5(b) is a diagram illustrating the resin curing process. In the following description and in Figure 5, the same reference numerals are used for the components of the concentrated joint electric wire 1 shown in Figure 1 or the components of the terminal-equipped electric wire 1A shown in Figures 2 and 3. In Figure 5(b), an example of the resin curing process is shown in which the curable resin R is cured by ultraviolet light W. However, the method is not limited to this, and the curable resin R may be cured by other means, such as heat.

[0115] The method for manufacturing the concentrated joint wire 1 involves stripping the insulating coating layers 12a to 12g covering each end of a plurality of insulated wires 10a to 10g, each having conductors 11a to 11g and insulating coating layers 12a to 12g covering the conductors 11a to 11g, thereby exposing the conductor portions 11a to 11g. The conductor exposed portions 14 are then bundled together and joined to form a joint portion 15. This manufacturing method includes a resin immersion step of immersing at least the joint portion 15 in an outer resin portion 17 filled with a curable resin R, and a resin curing step of curing the curable resin R in which at least the joint portion 15 is immersed in the outer resin portion 17 to form an inner resin portion 16, thereby integrally forming a covering resin portion 18 composed of the inner resin portion 16 and the outer resin portion 17 in a state of close contact over at least the entire outer peripheral surface 15a of the joint portion 15. The resin curing step involves curing the curable resin such that the gel fraction after heating, which is the gel fraction after a heating test of heating at 120°C for 1 hour, is higher than the gel fraction before heating, which is the gel fraction before the heating test.

[0116] Thus, after performing a resin immersion step in which the joint portion 15 of the coated electric wires 10a to 10g is immersed in a curable resin R filled in the outer resin portion 17, when curing the curable resin R in which the joint portion 15 is immersed to form the inner resin portion 16 in the resin curing step, the curable resin R is cured such that the gel fraction after heating, which is the gel fraction after a heating test of heating at 120°C for 1 hour, is higher than the gel fraction before heating, which is the gel fraction before the heating test. This allows for a reduction in the heating time when forming the cured resin, even when forming a thick cured resin. Furthermore, because the gel fraction of the cured resin increases due to the temperature rise around the concentrated joint electric wire 1 after wiring, it is possible to further cure it, thereby improving the watertightness against the penetration of moisture into the conductor portion.

[0117] The manufacturing method for this concentrated joint electric wire 1 comprises at least a resin immersion step and a resin curing step.

[0118] [Resin immersion process] The resin immersion process, as shown in Figure 5(a), involves immersing at least the joint portion 15 into the outer resin portion 17 filled with the aforementioned curable resin R. This brings the joint portions 15 of the insulated wires 10a to 10g into contact with the curable resin R held within the outer resin portion 17.

[0119] [Resin curing process] As shown in Figure 5(b), the resin curing process involves curing a curable resin R, in which at least the joint portion 15 is immersed, within the outer resin portion 17 to form an inner resin portion 16. This process integrally forms a covering resin portion 18, composed of the inner resin portion 16 and the outer resin portion 17, in close contact with at least the entire outer peripheral surface 15a of the joint portion 15. As a result, the curable resin R in contact with the outside of the joint portion 15 hardens to form the inner resin portion 16, thereby enabling the formation of a covering resin portion 18, composed of the inner resin portion 16 and the outer resin portion 17, on the joint portion 15.

[0120] In this resin curing process, the curable resin R is cured such that the post-heating gel fraction, which is the gel fraction after a heating test of heating at 120°C for 1 hour, is higher than the pre-heating gel fraction, which is the gel fraction before the heating test. As a result, it is not necessary to completely cure the curable resin R in the resin curing process, and the time required to cure the curable resin R and form the inner resin portion 16 can be shortened. Furthermore, since the resulting inner resin portion 16 becomes even more cured by heating, the rise in ambient temperature after wiring allows the resin deep within the inner resin portion 16 to harden sufficiently, thereby improving the watertightness against the penetration of moisture into the conductive portion.

[0121] Furthermore, in this resin curing process, it is preferable to cure the curable resin R using at least one curing method from heat curing, ultraviolet curing, moisture curing, and anaerobic curing. At this time, it is even more preferable to cure the curable resin R by using heat curing in combination with at least one of ultraviolet curing, moisture curing, and anaerobic curing. This allows the oligomer and reactive diluent to polymerize not only due to heat, but also due to ultraviolet light, moisture, or contact with metal, thus shortening the time required to cure the curable resin R and form the inner resin portion 16. In particular, by using heat curing in combination with at least one of ultraviolet curing, moisture curing, and anaerobic curing, the degree of crosslinking of the curable resin can be adjusted by heat curing after curing the curable resin R to form the inner resin portion 16 made of cured resin, while leaving the thermal polymerization initiator to further increase the degree of crosslinking of the cured resin. This further shortens the time required to cure the curable resin R and form the inner resin portion 16.

[0122] Furthermore, in this resin curing process, it is preferable to heat the curable resin R for a time of 80% or less of the complete heat curing time of the curable resin R. This allows the thermal polymerization initiator contained in the curable resin R to remain in order to further increase the degree of crosslinking of the cured resin, and the cured resin can be further cured by the temperature rise around the concentrated joint wire 1 after wiring, thereby improving the watertightness against the penetration of moisture into the conductor portion.

[0123] <Manufacturing method for wires with terminals> Figure 6 shows an example of a method for manufacturing a terminal-equipped electric wire according to the present invention. Figure 6(a) is a diagram illustrating the resin coating process, and Figure 6(b) is a diagram illustrating the resin curing process. In the following description and in Figure 6, the same reference numerals are used for the components used in the manufacturing method of the concentrated joint electric wire 1 shown in Figure 1, the terminal-equipped electric wire 1A shown in Figures 2 and 3, or the concentrated joint electric wire 1 shown in Figure 5. In addition, Figure 6(b) shows an example of a resin curing process in which a curable resin R is cured by ultraviolet light W, but the method is not limited to this, and the curable resin R may be cured by other means, such as heat.

[0124] The method for manufacturing a terminal-equipped electric wire 1A is a method for manufacturing a terminal-equipped electric wire in which a metal terminal 20 is electrically connected to the conductor portion exposed by stripping the insulating coating layer 12 covering the end of a coated electric wire 10, which has an insulating coating layer 12 covering the surface of a conductor 11. This manufacturing method includes a resin coating step of coating and forming a curable resin R on the outer surface of at least the exposed conductor portion of the coated electric wire 10, and a resin curing step of curing the curable resin R to form a cured resin, thereby integrally forming a coated resin portion 18A composed of the cured resin in close contact with at least the exposed conductor portion of the coated electric wire 10. The resin curing step involves curing the curable resin R such that the gel fraction after heating, which is the gel fraction after a heating test of heating at 120°C for 1 hour, is higher than the gel fraction before heating, which is the gel fraction before the heating test.

[0125] Thus, after performing a resin coating step in which a curable resin R is coated onto the outer surface of the exposed conductor portion 11 of the coated wire 10, when curing the curable resin R coated onto the outer surface of the exposed conductor portion of the coated wire 10 to form the inner resin portion 16, the curable resin R is cured such that the gel fraction after heating, which is the gel fraction after heating at 120°C for 1 hour, is higher than the gel fraction before heating, which is the gel fraction before heating. This allows for a reduction in the heating time when forming the cured resin, even when forming a thick cured resin. Furthermore, the gel fraction of the cured resin increases due to the temperature rise around the terminal-equipped wire 1A after routing, leading to further curing and improved watertightness.

[0126] The manufacturing method for this concentrated joint electric wire 1 comprises at least a resin coating step and a resin curing step.

[0127] [Resin coating process] The resin coating process, as shown in Figure 6(a), involves coating the outer surface of at least the exposed conductor portion of the coated wire 10 with a curable resin R. As a result, the outer surface of the exposed portion of the conductor 11 of the coated wire 10 is covered with the curable resin R.

[0128] In the resin coating process, the conductor 11 is crimped at the wire crimping section 23, and the insulating coating layer 12 is crimped at the coating crimping section 25. The coated wire 10 and metal terminal 20 are electrically connected, and the above-mentioned curable resin R is applied to the portion of the conductor 11 that is exposed from the barrel section 24 to the wire crimping section 23, using a dispenser 40 or the like. If the viscosity of the curable resin R is 50 Pa·s or less, the curable resin R can be made to adhere closely to the conductor 11 by penetrating it to the underside of the conductor 11 due to its own weight. If the viscosity of the curable resin R exceeds 50 Pa·s, after applying the above-mentioned curable resin R, the curable resin R can be made to adhere closely to the underside of the conductor 11 by pressing it against the conductor 11 using a spatula or the like.

[0129] [Resin curing process] As shown in Figure 6(b), the resin curing process involves curing a curable resin R to form a cured resin, thereby integrally forming a coating resin portion 18A composed of the cured resin, which is in close contact with at least the exposed conductor portion of the insulated wire 10. As a result, the curable resin R in contact with the outer surface of the exposed portion of the conductor 11 of the insulated wire 10 hardens to form the coating resin portion 18A, and this coating resin portion 18A can improve watertightness against the penetration of moisture into the conductor portion.

[0130] In this resin curing process, the curable resin R is cured such that the post-heating gel fraction, which is the gel fraction after a heating test of heating at 120°C for 1 hour, is higher than the pre-heating gel fraction, which is the gel fraction before the heating test. As a result, it is not necessary to completely cure the curable resin R in the resin curing process, and the time required to cure the curable resin R and form the coating resin portion 18A can be shortened. Furthermore, since the resulting coating resin portion 18A hardens further with heating, the resin deep within the coating resin portion 18A can be sufficiently cured by the rise in ambient temperature after wiring, thereby improving the watertightness against the penetration of moisture into the conductive portion.

[0131] Furthermore, in this resin curing process, it is preferable to cure the curable resin R using at least one curing method from heat curing, ultraviolet curing, moisture curing, and anaerobic curing. At this time, it is even more preferable to cure the curable resin R by using heat curing in combination with at least one of ultraviolet curing, moisture curing, and anaerobic curing. This allows the oligomers and reactive diluents contained in the curable resin R to polymerize due to heat, ultraviolet light, moisture, or contact with metal, thus shortening the time required to cure the curable resin R and form the coating resin portion 18A. In particular, by using heat curing in combination with at least one of ultraviolet curing, moisture curing, and anaerobic curing, the degree of crosslinking of the curable resin can be adjusted by heat curing after curing the curable resin R to form the coating resin portion 18A made of cured resin, while leaving the thermal polymerization initiator to further increase the degree of crosslinking of the cured resin. This further shortens the time required to cure the curable resin R and form the coating resin portion 18A.

[0132] Furthermore, in this resin curing process, it is preferable to heat the curable resin R for a time of 80% or less of the complete heat curing time of the curable resin R. This allows the thermal polymerization initiator contained in the curable resin R to remain to further increase the degree of crosslinking of the cured resin, and the cured resin can be further cured by the temperature rise around the terminal-equipped wire 1A after wiring, thereby improving the watertightness against the penetration of moisture into the conductor portion. [Examples]

[0133] Next, in order to further clarify the effects of the present invention, examples and comparative examples of the present invention will be described, but the present invention is not limited to these examples.

[0134] [1] Fabrication of concentrated jointed electric wires Cross-sectional area 0.75sq(0.75mm 2 Two copper wires of 0.75 sq (0.75 mm²) cross-sectional area. 2The insulating coating layer covering each end of four insulated wires, each consisting of two aluminum wires, was stripped to a length of 20 mm to expose the conductor portion, and the conductor portions of these four insulated wires were bundled together to form a splice wire, which was then joined and integrated using ultrasonic welding to form a joint.

[0135] Next, a resin immersion process was performed in which a curable resin, formulated with the composition (parts by mass) shown in Table 1, was filled into the outer resin portion, which consisted of a transparent polypropylene resin container with an inner diameter of 5 mm, a height of 30 mm, and a thickness t' of 1 mm (ultraviolet light transmittance at a wavelength of 365 nm: 68%), and the joint portion of the exposed conductor of the insulated wire was immersed in the curable resin filled into the outer resin portion. Subsequently, for Examples 1 to 6, 8 and Comparative Examples 2 and 3 of the present invention, ultraviolet light at a wavelength of 365 nm was applied from the outer surface of the transparent container, which is the outer resin portion, at a rate of 500 mW / cm². 2 A concentrated joint wire was manufactured by performing a resin curing process in which the curable resin in which the joint portion was immersed was cured by irradiating it with the intensity shown in Table 1 for the time and number of times shown, thereby forming the inner resin portion within the outer resin portion, and then heating it at the temperature and time shown in Table 1 to further cure the curable resin. In addition, for Examples 7 and 9 of the present invention, a concentrated joint wire was manufactured by performing a resin curing process in which the curable resin was further cured by heating it at the temperature and time shown in Table 1 without irradiation with ultraviolet light. In addition, for Comparative Example 1, ultraviolet light with a wavelength of 365 nm was irradiated from the outer surface of the transparent container, which is the outer resin portion, at a rate of 500 mW / cm². 2 By irradiating the joint with the curable resin immersed in the joint at the intensity shown in Table 1 for the duration and number of times, the inner resin portion was cured and formed within the outer resin portion. After that, the concentrated joint wire was fabricated without further curing of the curable resin by heating. The thickness t of the cured resin constituting the inner resin portion was measured by cutting a cross section from the concentrated joint wire along the thickness direction of the cured resin, polishing the resulting cross section to make it smooth, observing the smoothed cross section with a microscope, and measuring the thickness using the microscope's measurement function. The results are shown in Table 1.

[0136] [2] Preparation of wires with terminals Cross-sectional area 8sq(8mm2 ) An insulating coating layer covering an end portion of a covered electric wire made of an aluminum electric wire having a length of 100 mm was stripped over a length of 10 mm to expose a conductor portion, and an open barrel terminal made of tin-plated copper as a metal terminal was crimped to the exposed conductor portion. Here, the insulating coating layer of the covered electric wire was crimped by the coating crimping portion of the metal terminal, and the conductor exposed by stripping the insulating coating layer was crimped by the conductor crimping portion.

[0137] Next, a curable resin having a viscosity of about 10 Pa·s formulated with the composition (parts by mass) shown in Table 2 was applied to the entire outer surface of the exposed conductor portion of the covered electric wire using a dispenser, and the curable resin R was allowed to permeate to the lower side of the conductor 11 under its own weight, thereby performing a resin coating step of bringing the curable resin R into close contact with the conductor 11. Thereafter, for Invention Examples 10 to 15, 17 and Comparative Examples 5 and 6, ultraviolet light having a wavelength of 365 nm was applied from the outside of the curable resin at 500 mW / cm 2 After the curable resin was cured by irradiation at the intensity for the time and number of times shown in Table 2, a resin curing step was performed in which the curable resin was cured by heating at the temperature and for the time shown in Table 2 to form a coated resin portion, thereby producing an electric wire with a terminal. For Invention Examples 16 and 18, an electric wire with a terminal was produced by performing a resin curing step of further curing the curable resin by heating at the temperature and for the time shown in Table 1 without ultraviolet irradiation. For Comparative Example 4, ultraviolet light having a wavelength of 365 nm was applied from the outer surface side of the transparent container as the outer resin portion at 500 mW / cm 2 By irradiating at the intensity for the time and number of times shown in Table 1 to cure the curable resin in which the joint portion was immersed to form the inner resin portion inside the outer resin portion, an electric wire with a terminal was produced without further curing the curable resin by heating. In the obtained electric wire with a terminal, the length of the portion facing the range from the end to the bottom of the inner wall of the metal terminal was determined by cutting out a cross section perpendicular to the extending direction of the conductor at the position of a plane crossing the opening between the barrels of the metal terminal of the electric wire with a terminal, polishing the obtained cross section to be smooth, observing the smoothed cross section with a microscope, and measuring the thickness using the measurement function of the microscope. The results are shown in Table 2.

[0138] [3] Detailed composition of each component used in the curing resin The detailed composition of each component used in the preparation of the curable resins listed in Tables 1 and 2 is as follows. In Tables 1 and 2, the content of photopolymerization initiators, thermal radical polymerization initiators, and antioxidants is listed per 100 parts by mass of the curable component of the curable resin.

[0139] [(meth)acrylate monomer] • Photo-radical polymerizable acrylate monomer: Isobornyl acrylate (manufactured by Nippon Shokubai Co., Ltd., product name: Isobornyl acrylate)

[0140] [Reactive Diluent] • Acryloylmorpholine (manufactured by KJ Chemicals Co., Ltd., product name: ACMO)

[0141] [Photopolymerization initiator] • Photoradical polymerization initiator: 1-Hydroxycyclohexyl phenyl ketone (IGM Resins product name: Omnirad 184)

[0142] [Thermal radical polymerization initiator] • Thermal radical polymerization initiator: 2,5-dimethyl-2,5-di(2-ethylhexanoylperoxy)hexane (manufactured by NOF Corporation, product name: Perhexa 250, half-life temperature at 1 minute: 118.8℃)

[0143] [Antioxidant] • Phenol antioxidant: 2,4-dimethyl-6-(1-methylpentadecyl)phenol (BASF, product name: Irganox 1141)

[0144] [4] Measurement of gel fraction For each of the centralized joint wires and terminal-equipped wires of the present invention example and comparative example, 0.5 g of the cured resin constituting the inner resin portion was taken in accordance with JIS-K-6796 and immersed in methyl ethyl ketone at room temperature for 24 hours. The gel fraction [%] was calculated as the ratio of the mass difference of the cured resin before and after immersion (B) to the mass of the cured resin (A) ((B / A) × 100), and this was taken as the gel fraction (C) before the heating test.

[0145] Furthermore, for each of the concentrated joint wires and terminal-equipped wires of the present invention example and comparative example, a heating test was performed by heating at 120°C for 1 hour. Then, 0.5 g of the cured resin constituting the inner resin portion was similarly taken and immersed in methyl ethyl ketone at room temperature for 24 hours. The gel fraction [%] was calculated as the ratio of the mass difference of the cured resin before and after immersion (B') to the mass of the cured resin (A') ((B' / A') × 100), and this was taken as the gel fraction (C') after the heating test.

[0146] From the gel fraction values ​​before and after these heating tests, the difference (C'-C) between the gel fraction before the heating test (C) and the gel fraction after the heating test (C') was calculated. The results are shown in Tables 1 and 2.

[0147] [5] Evaluation of water-sealing properties For concentrated joint wires, the concentrated joint wires of the present invention example and the comparative example were used as test materials, and the resistance value between the two conductors was measured for all possible combinations of two conductors selected from the multiple conductors constituting the concentrated joint wire. The average of all combinations was taken as the measured resistance value. However, if the concentrated joint wire consisted of five or more conductors, four conductors were randomly selected from the five or more conductors, and the average of the resistance values ​​when all combinations of two conductors from these four conductors were measured was taken as the measured resistance value. Furthermore, for wires with terminals, the wires with terminals of the present invention example and the comparative example were used as test materials, and the resistance value of the portion where the metal terminal and the wire conductor are crimped was measured. This measured value was taken as the resistance value (D) before the liquid resistance test. Subsequently, for each test material after the resistance value measurement, a liquid resistance test was performed by immersing it for 120 minutes in the following types and temperatures of test liquids A to C, which simulate the surrounding environment of the concentrated joint wire or wire with terminals after wiring.

[0148] (Type of test solution and temperature) Test solution A: Antifreeze (manufactured by Furukawa Chemical Industries, Ltd., product name: Long Life Coolant JIS), temperature 120℃ Test fluid B: Automatic transmission fluid (manufactured by Idemitsu Kosan Co., Ltd., product name: Apollo station oil ATF / CVTF), temperature 90℃ Test solution C: Window washer fluid (manufactured by Furukawa Chemical Industries, Ltd., product name: KYK Window Washer Fluid), temperature 60℃

[0149] After conducting liquid resistance tests using test solutions A to C, the test specimens were removed from the test solutions and allowed to dry at room temperature for 24 hours. Subsequently, each test specimen was immersed in a 3% by mass sodium chloride aqueous solution at room temperature for 96 hours, and then dried in the air for 24 hours. The resistance value of each test specimen was measured using the same method as before immersion in the aqueous solution, and this measured value was defined as the resistance value after the liquid resistance test (D').

[0150] From the resistance values ​​before and after these liquid resistance tests, the increase in resistance value (D'-D) after the liquid resistance test (compared to the resistance value (D) before the test (D) was calculated for each of the following tests: before and after using test liquid A, before and after using test liquid B, and before and after using test liquid C. This was then evaluated according to the following evaluation criteria. The results are shown in Tables 1 and 2.

[0151] (Evaluation criteria for the increase in resistance value before and after liquid resistance testing) ◎: When the increase in resistance value (D'-D) before and after the liquid resistance test is 10 mΩ or less. ○: When the increase in resistance value (D'-D) before and after the liquid resistance test exceeds 10 mΩ and is 30 mΩ or less. △: When the increase in resistance value (D'-D) before and after the liquid resistance test exceeds 30 mΩ and is 100 mΩ or less. ×: When the increase in resistance value (D'-D) before and after the liquid resistance test exceeds 100 mΩ.

[0152] [6] Evaluation of water resistance (waterproofness) For the concentrated joint wires of the present invention example and comparative example, in the apparatus configuration shown in Figure 7, the concentrated joint wire 1 was submerged in water H held in the experimental container 52, and air was injected at a pressure of 200 kPa from one end of any one of the four insulated wires (two copper wires and two aluminum wires) 13a using a pump 51, along the air flow direction F shown in Figure 7, and the presence or absence of air leaks AL from the insulated resin part 18 and the other insulated wires 13b to 13d other than the wire into which air was injected into the water H was observed. If no air leaks AL were detected from the coated resin part 18 or any of the other coated wires 13b to 13d, the water-sealing evaluation result was evaluated as "◎". If air leaks AL were detected from only one of the other coated wires 13b to 13d, the water-sealing evaluation result was evaluated as "〇". If air leaks AL were detected from two of the other coated wires 13b to 13d, the water-sealing evaluation result was evaluated as "△". On the other hand, if air leaks AL were detected from all three of the other coated wires 13b to 13d, or if air leaks AL were detected from the coated resin part 18, the water-sealing evaluation result was evaluated as "×" as a failure. The results are shown in Tables 1 and 2.

[0153] [7] Overall rating Of these evaluation results, for the water-sealing evaluation, if the evaluation result for the increase in resistivity after the liquid resistance test using test liquid A (antifreeze, 120°C) was "◎", "○", or "△", and both the evaluation result for the increase in resistivity after the liquid resistance test using test liquid B (automatic transmission fluid, 90°C) and the evaluation result for the increase in resistivity after the liquid resistance test using test liquid C (windshield washer fluid, 60°C) were "◎", then the water-sealing performance was evaluated as "◎". In addition, if the evaluation result for the increase in resistivity after the liquid resistance test using test liquid A was "○" or "△", and one or both of the evaluation results for the increase in resistivity after the liquid resistance test using test liquid B and the evaluation result for the increase in resistivity after the liquid resistance test using test liquid C were evaluated as "○", then the water-sealing performance was evaluated as "○", then the water-sealing performance was evaluated as "◎". Furthermore, if the evaluation result of the increase in resistivity after the liquid resistance test using test solution A was "△", and one or both of the evaluation results of the increase in resistivity after the liquid resistance test using test solution B and the evaluation results of the increase in resistivity after the liquid resistance test using test solution C were evaluated as "△", and the remaining one was evaluated as "◎" or "○", then the water-sealing ability was considered acceptable and evaluated as "△". On the other hand, if at least one of the evaluation results of the increase in resistivity after the liquid resistance test using test solution A, the evaluation results of the increase in resistivity after the liquid resistance test using test solution B, and the evaluation results of the increase in resistivity after the liquid resistance test using test solution C were evaluated as "×", or if the liquid resistance test could not be performed using at least one of test solutions A to C, then the water-sealing ability was considered unacceptable and evaluated as "×". The results are shown in Tables 1 and 2.

[0154] [Table 1]

[0155] [Table 2]

[0156] From the above results, it was confirmed that the concentrated joint electric wires of the present invention examples 1 to 9 are equipped with an inner resin portion made of cured resin in which the post-heating gel fraction, which is the gel fraction after a heating test of heating at 120°C for 1 hour, is higher than the pre-heating gel fraction, which is the gel fraction before the heating test. In this case, even if the cured resin is thick, the inner resin portion can be obtained in a short curing time, and the watertightness against the intrusion of moisture into the conductor portion can be improved by temperature conditions that are assumed to be the surrounding environment of the concentrated joint electric wire after wiring.

[0157] Furthermore, the terminal-equipped wires of the present invention examples 10 to 18 also have a coating resin portion made of a cured resin in which the post-heating gel fraction, which is the gel fraction after a heating test of heating at 120°C for 1 hour, is higher than the pre-heating gel fraction, which is the gel fraction before the heating test. In this case, even if the cured resin is thick, the coating resin portion can be obtained in a short curing time, and it has been confirmed that the watertightness against the intrusion of moisture into the conductor portion can be improved by temperature conditions that are assumed to be the surrounding environment of the terminal-equipped wire after wiring.

[0158] On the other hand, the concentrated joint wire of Comparative Example 1 and the terminal-equipped wire of Comparative Example 4 are examples in which the curable resin does not contain a thermal polymerization initiator, and even when a heating test is performed by heating at 120°C for 1 hour, the gel fraction does not increase. In these examples, the evaluation of the increase in resistivity after a liquid resistance test simulating the surrounding environment after wiring was all evaluated as "×", and even under temperature conditions simulating the surrounding environment after wiring, it was not possible to improve the watertightness against the intrusion of moisture into the conductor portion.

[0159] Furthermore, the centralized joint wire in Comparative Example 2 and the terminal-equipped wire in Comparative Example 5 both used 2,5-dimethyl-2,5-di(2-ethylhexanoylperoxy)hexane, which has a 1-minute half-life temperature of 118.8°C, as a thermal polymerization initiator, and were heated at a heating temperature of 120°C for 10 minutes during the resin curing process. In these examples, theoretically, 99.9% of the thermal radical polymerization initiator decomposes, and even after a heating test of heating at 120°C for 1 hour, the gel fraction does not increase. In particular, the evaluation of the increase in resistivity after the liquid resistance test using automatic transmission fluid at 90°C and antifreeze at 120°C was both evaluated as "×", indicating that the watertightness against the intrusion of moisture into the conductor portion could not necessarily be improved under temperature conditions that simulate the surrounding environment after wiring. [Explanation of Symbols]

[0160] 1. Concentrated joint wire 1A wire with terminal 10, 10a~10g, 13a~13d insulated wires 11, 11a~11g Conductors 12, 12a~12g Insulating coating layer 14. Exposed conductor portion 15 Joint 15a Outer surface of the joint 16 Inner resin part 16a Outer surface of the inner resin portion 17 Outer resin part 18, 18A Coated resin part 20 metal terminal 20a Inner wall of metal terminal 20b End of metal terminal 20c metal terminal bottom 21 Terminal body 22 Transition Section 23 Wire crimping section 24 Barrel section 25 Cover crimping part 26 Elastic contact piece 40 dispensers 51 Pump 52 experimental containers t Thickness of cured resin t' Thickness of the outer resin part Direction of extension of the conductor X L: The length of the portion facing the inner wall of the metal terminal, from the end to the bottom. R curable resin W UV AL Air Leak H water F Airflow direction

Claims

1. It consists of a plurality of insulated wires, each having a conductor and an insulating coating layer covering the conductor. A concentrated joint wire having a joint formed by stripping the insulating coating layer covering each end of the plurality of insulated wires to expose the conductor portion at the end, and then joining and integrating the exposed conductor portions in a bundled state, The aforementioned concentrated joint wire is An inner resin portion made of cured resin is integrally formed with the joint portion in a state of close contact over at least the entire outer surface of the joint portion, An outer resin portion that is integrally formed in close contact with at least the entire outer surface of the inner resin portion and It has a coating resin part made of the following: The cured resin is a concentrated joint electric wire in which the gel fraction after heating, which is the gel fraction after a heating test in which it is heated at 120°C for 1 hour, is higher than the gel fraction before heating, which is the gel fraction before the heating test.

2. The concentrated joint electric wire according to claim 1, wherein the gel fraction of the cured resin after heating is 12.5% ​​or more higher than the gel fraction before heating.

3. The concentrated joint electric wire according to claim 2, wherein the gel fraction of the cured resin after heating is 25.0% or more higher than the gel fraction before heating.

4. The concentrated joint electric wire according to claim 3, wherein the gel fraction of the cured resin after heating is 50.0% or more higher than the gel fraction before heating.

5. The concentrated joint wire according to claim 1, wherein the curing resin is a thermosetting resin.

6. The concentrated joint wire according to claim 5, wherein the curing resin further has one or more curing properties from ultraviolet curing, moisture curing, and anaerobic curing.

7. The concentrated joint electric wire according to claim 1, wherein the inner resin portion has a thickness in the range of 3.0 mm to 15.0 mm.

8. A covered wire in which an insulating coating layer is applied to the surface of the conductor, A metal terminal electrically connected to the conductor portion exposed by stripping the insulating coating layer covering the end of the insulated wire, A wire with terminals equipped with, At least the outer surface of the exposed conductor portion of the insulated wire is covered with a coating resin portion made of a hardened resin. The cured resin is a wire with terminals, wherein the gel fraction after heating, which is the gel fraction after a heating test in which it is heated at 120°C for 1 hour, is higher than the gel fraction before heating, which is the gel fraction before the heating test.

9. The terminal wire according to claim 8, wherein the gel fraction of the cured resin after heating is 12.5% ​​or more higher than the gel fraction before heating.

10. The terminal-equipped wire according to claim 9, wherein the gel fraction of the cured resin after heating is 25.0% or more higher than the gel fraction before heating.

11. The terminal-equipped wire according to claim 10, wherein the gel fraction of the cured resin after heating is 50.0% or more higher than the gel fraction before heating.

12. The terminal-equipped wire according to claim 8, wherein the curing resin is a thermosetting resin.

13. The terminal-equipped wire according to claim 12, wherein the curing resin further has one or more curing properties selected from ultraviolet curing, moisture curing, and anaerobic curing.

14. The wire with terminal according to claim 8, wherein the length of the portion of the covering resin that faces the area from the end to the bottom of the inner wall of the metal terminal is in the range of 3.0 mm to 15.0 mm.

15. A wire harness comprising one or both of the centralized joint wires according to any one of claims 1 to 7 and the terminal wires according to any one of claims 8 to 14.

16. A method for manufacturing a concentrated joint wire having a joint formed by stripping the insulating coating layer covering each end of a plurality of insulated wires, each having a conductor and an insulating coating layer covering the conductor, thereby exposing the conductor portion at the end, and then bundling and joining the exposed conductor portions together, A resin immersion step in which at least the joint portion is immersed in an outer resin portion filled with a curable resin, A resin curing step is performed in which the curable resin, in which at least the joint portion is immersed, is cured within the outer resin portion to form an inner resin portion, thereby integrally forming a covering resin portion composed of the inner resin portion and the outer resin portion in close contact with at least the entire outer surface of the joint portion. Includes, A method for manufacturing a concentrated joint electric wire, wherein the resin curing step involves curing the curable resin such that the post-heating gel fraction, which is the gel fraction after a heating test of heating at 120°C for 1 hour, is higher than the pre-heating gel fraction, which is the gel fraction before the heating test.

17. The method for manufacturing a concentrated joint electric wire according to claim 16, wherein the resin curing step involves curing the curable resin using at least one curing means from heat curing, ultraviolet curing, moisture curing, and anaerobic curing.

18. The method for manufacturing a concentrated joint electric wire according to claim 17, wherein the heat curing in the resin curing step involves heating the curable resin for a time of 80% or less of the complete heat curing time of the curable resin.

19. A method for manufacturing a wire with terminals, comprising: electrically connecting a metal terminal to a conductor portion that is exposed by stripping the insulating coating layer covering the end of a coated wire, in which an insulating coating layer is covered on the surface of the conductor; A resin coating step is to coat and form a curable resin on at least the outer surface of the exposed conductor portion of the insulated wire, A resin curing process in which the curable resin is cured to form a cured resin, thereby integrally forming a coating resin portion composed of the cured resin in close contact with at least the exposed conductor portion of the coated electric wire. Includes, A method for manufacturing an electric wire with terminals, wherein the resin curing step involves curing the curable resin such that the post-heating gel fraction, which is the gel fraction after a heating test of heating at 120°C for 1 hour, is higher than the pre-heating gel fraction, which is the gel fraction before the heating test.

20. The method for manufacturing a wire with a terminal according to claim 19, wherein the resin curing step involves curing the curable resin using at least one curing means from heat curing, ultraviolet curing, moisture curing, and anaerobic curing.

21. The method for manufacturing a wire with terminals according to claim 20, wherein the heat curing in the resin curing step involves heating the curable resin for a time of 80% or less of the complete heat curing time of the curable resin.

Citation Information

Patent Citations

  • Quinodimethane compound

    JP1987000448A